Mori Nori (Moringa oleifera innovation into healthy nori snacks) - Fahrezi, Dimas; Raharjo, Gita Tresno Asih; Sari, Olga Octaviani Eka; Hanum, Paujia; Hidayatullah, Syarif (2025)
Moringa leaves (Moringa oleifera) are known to the public as wild plants that were once less than optimally utilized, despite having very high nutritional content. Along with the development of public awareness about the importance of functional and healthy food, the benefits of moringa began to receive attention. Mori Nori products were introduced as a healthy food innovation based on moringa leaves produced without preservatives and MSG and processed through burning/roasting to preserve their original flavour and nutritional content. Then, it is processed into nori chips as an alternative to the conventional nori based on seaweed. By combining the distinctive flavour of moringa and the practical form of nori, Mori Nori aims to introduce moringa in a more modern, attractive, nutritious, natural, and edible form to the public, especially to the younger generation. The methods used include formulation of ingredient mixtures, drying and baking techniques, and organoleptic testing of taste, aroma, and texture. The results obtained show that Mori Nori has good organoleptic quality and nutritional content that is permanently preserved. This innovation is expected to be a major and successful contribution in the diversification of local foods as well as the development of high economic value products that will become healthy food solutions based on Indonesia's natural wealth.